Centralized PID control by decoupling for TITO processes - Morilla, F.; Vazquez, F.; Garrido, J. (2008 IEEE International Conference on Emerging Technologies and Factory Automation, 2008)
This paper presents a new methodology to design multivariable PID controllers for two-input and two-output systems. The proposed control strategy, which is centralized, combines four PID controllers plus two possible delays and two P controllers. The proportional gains in the P controllers act as tuning parameters in order to modify the behavior of the loops almost independently. The design procedure consists of three steps: first, an ideal decoupler including integral action is determined. Second, the decoupler is approximated with four PID controllers plus two possible delays. Third, the proportional gains are tuned to achieve the specified performance. The proposed method is applied to three representative processes.